Student Well-Being in Islamic Religious Education Learning in the Digital Era: A Phenomenological Study - Nur Muhammad Gasmi; Nanang Supriadi; Baharudin Baharudin (Universitas Islam Lamongan, 2026)
Digital transformation in Islamic Religious Education (IRE) learning has not only altered pedagogical strategies but also reshaped students' Well-being experiences. This study aims to examine the meaning of student Well-being and the factors influencing it in IRE learning in the digital era. This research employed a qualitative, phenomenological design. The findings reveal that student Well-being is interpreted as a holistic construct encompassing academic balance, emotional comfort, quality of social relationships, and spiritual meaningfulness within IRE learning. Well-being is shaped by the interaction of pedagogical practices, peer relationships, the design and workload of digital learning, students' self-regulation in technology use, family support, and school-based spiritual practices. The novelty of this study lies in the formulation of a conceptual model of student Well-being in IRE grounded in students' perspectives, integrating pedagogical, digital, and spiritual dimensions simultaneously within a learning ecosystem framework that implies the need to develop IRE learning practices oriented toward holistic and sustainable Well-being in the digital era.